Genre Analysis of Efl Students’ Writing Descriptive Text On Instagram - Mochamad Fiqri Fauzi; Abdul Kodir Al-Baekani; Yogi Setia Samsi (Innovative: Journal Of Social Science Research, 2023)
The purpose of this study was to explore EFL students' writing of descriptive text through Instagram by adding genre analysis and students' responses. This research uses the narrative inquiry method with a qualitative approach. In this study researchers took VII students as subjects. Researchers use observation and interview as research instruments. The results of this study show that there are still some students who still have difficulty in writing descriptive texts because of the lack of vocabulary they master. The use of the Instagram application in writing descriptive text provides a sense of fun and fun for students and makes it easier for students to develop themselves and can share it with their virtual friends. Based on the results of the study, it can be concluded that the problem faced by students is that there are still difficulties in writing English. It is recommended for English teachers that teachers can memorize repetitive vocabulary to students and teachers are even more creative in improving vocabulary teaching methods.